Serum detection of IgG antibodies against Demodex canis by western blot in healthy dogs and dogs with juvenile generalized demodicosis. (August 2015) - Ravera, Ivan; Ferreira, Diana; Gallego, Laia Solano; Bardagí, Mar; Ferrer, Lluís
Abstract: The aim of this study was to investigate the presence of canine immunoglobulins (Ig) G against Demodex proteins in the sera of healthy dogs and of dogs with juvenile generalized demodicosis (CanJGD) with or without secondary pyoderma. Demodex mites were collected from dogs with CanJGD. Protein concentration was measured and a western blot technique was performed. Pooled sera from healthy dogs reacted mainly with antigen bands ranging from 55 to 72 kDa. Pooled sera from dogs with CanJGD without secondary pyoderma reacted either with 10 kDa antigen band or 55 to 72 kDa bands. Pooled sera from dogs with CanJGD with secondary pyoderma reacted only with a 10 kDa antigen band. The results of this study suggest that both healthy dogs and dogs with CanJGD develop a humoral response against different proteins of Demodex canis . Highlights: Demodex mites were obtained and protein was extracted. Western blot was performed. Healthy dogs and dogs with CanJGD showed IgG antibodies against Demodex proteins.